PERAN SATUAN POLISI PAMONG PRAJA DALAM PENATAAN PEDAGANG KAKI LIMA (PKL) DI PASAR TUAH SERUMPUN KECAMATAN TUALANG KABUPATEN SIAK TAHUN 2021 - Susmita Yulia Putri; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Looking at the authority given to the Civil Service Police Unit, it is undeniable that the existence of the Civil Service Police Unit is very important and strategic in the administration of regional government in accordance with its scope of duties, including the implementation of public order and public peace. The focus topic of this research is "The Role of Satpol PP in Structuring Street Vendors (PKL) At Tuah Serumpun Market, Tualang Resident of Siak in 2021", the problem raised in this study is How the Role of Civil Service Police Unit in Five Feet (PKL) At Tuah Serumpun Market? And what are the inhibiting factors for Civil Service Police Unit in the arrangement of Five Feet (PKL) at Tuah Serumpun Market, Tualang District Siak Resident? The purpose of this study is to find out how the role of Civil Service Police Unit in Five Feet at Tuah Serumpun Market. The research method used is a qualitative research method. The research location is in Perawang City, Tualang District. As for the informants in this study amounted to 5 people according to predetermined criteria (purposive sampling). The data collection techniques used are interviews and documentation, The role given by the Civil Service Police Unit in controlling the arrangement of five feet at Tuah Serumpun Market, Tualang Residentt is still not carried out optimally and the solution must be good coordination from the UPT Market Tualang Resident so that the role carried out by Civil Service Police Unit can be carried out properly and maximum because of the involvement of other agencies and help add enforcement personnel at the Serumpun Tuah Market. The inhibiting factor of Civil Service Police Unit in Five Feet (PKL) is the lack of Civil Service Police Unit personnel, many traders do not want to be moved for reasons of fear of losing their customers, then far from where they live, and they have to start looking for new customers again. Keywords: Role, Public Order Enforcers Police